Development of nano-satellite - image processing module - Kanika Bansal. (2012)
Velox-I is the premier nano-satellite being designed and built by the students of Nanyang Technological University and will be deployed into the Low Earth Orbit (LEO) in 2013. One of the objectives of the Velox-I mission is Earth observation. For this it is equipped with a CMOS Digital Image Sensor which will be used to provide high-resolution images of the Earth.